Invisible Mothers: Unseen yet Hypervisible After Incarceration. By Garcia-HallettJanet (University of California Press, 2022, 248pp. £30.00) - Michalsen, Venezia (The British Journal of Criminology, 2023)
Invisible Mothers: Unseen yet Hypervisible After Incarceration, the new book by Dr. Janet Garcia-Hallett, has almost innumerable contributions to the field. The first thing that the reader will likely notice that makes this work stand out is the impact of Garcia-Hallett’s positionality as an Afro-Latina mother on the holistic understanding of the experiences of the Black and brown women as mothers and victims of the racist American carceral system. Garcia-Hallett grew up in Harlem, witnessing the transformation of her community due to the takeover of the penal system. For this book, she interviewed 37 mothers in New York City with histories of incarceration, and her writing skilfully puts the reader in her shoes as she presents the findings from her interviews, which took place in their kitchens, booths in McDonald’s, and at tables in shelters. In her exploration of these women’s experiences, Garcia-Hallett departs from the traditional pitiful exploration of their lives, but instead, paints a complicated, multifaceted picture of women engaging actively in many different types of motherwork, while facing almost constant obstacles from racist and misogynist criminal legal and child welfare systems that criminalize, pathologize and penalize their survival of their marginalization, rather than helping ‘save’ children and their mothers. She provides a critical and structural analysis while also introducing each woman as deeply unique in her strengths and challenges and is able to acknowledge the importance of the children without letting them overshadow the mothers. This is no small feat.
Keywords: book.review; dept.soc

Intersectional Feminist Criminology: A Critical Companion to Theory and Research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic Critical perspectives on the topic Critical thinking breaks Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system.
Keywords: dept.soc

Mothering as a Life Course Transition: Do Women Go Straight for Their Children? - Michalsen, Venezia (Journal of Offender Rehabilitation, 2011)
In this study, qualitative, in-depth interviews were conducted with 100 formerly incarcerated mothers to explore the relationship between attachment to children and desistance from criminal behavior. Exploratory data analysis revealed that mothers do believe that children play important roles in their desistance, consistent with the tenets of life course theory. However, children were also described as sources of great stress, which may in turn promote criminal behavior. Women also related desistance to reliance on self and a higher power, and to a desire to avoid future involvement with the criminal justice system. The article concludes with a call for more research on women's desistance, and increased consideration of parent–child relationships in corrections policy decision making.
_eprint: https://doi.org/10.1080/10509674.2011.589887
Keywords: attachment; children; dept.soc; desistance; life course theory; mothers; peer-reviewed; reentry

A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Mothering and Desistance in Re-Entry - Michalsen, Venezia (Routledge, 2018)
Although there is plentiful research on the impact of marriage, employment and the military on desistance from criminal behaviour in the lives of men, far less
Keywords: dept.soc

Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed

Intersectional feminist criminology: A critical companion to theory and research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic. Critical perspectives on the topic. Critical thinking breaks. Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system. © 2025 by Venezia Michalsen. All rights reserved.
Keywords: dept.soc

Not All Women Are Mothers: Addressing the Invisibility of Women Under the Control of the Criminal Justice System Who Do Not Have Children - Michalsen, Venezia; Flavin, Jeanne (The Prison Journal, 2014)
Research has consistently shown that most women under the control of the criminal justice system are mothers. The robustness of this finding has been accompanied by a failure to consider the characteristics and needs of women without children. In this study, we examine data on 1,334 formerly incarcerated women. Findings indicate that while mothers and non-mothers share some characteristics, they differ on several others, most notably demographic profile, mental health, and timing of contacts with the criminal justice system. These results suggest a need to recognize the diversity among women offender groups, particularly when developing policies and programs need.
Keywords: dept.soc; peer-reviewed

More than Visiting Hours: Maintaining Ties Between Incarcerated Mothers and Their Children - Michalsen, Venezia; Flavin, Jeanne; Krupat, Tanya (Sociology Compass, 2010)
The majority of people in America’s prisons are the parents of minor children. Incarcerated mothers, in particular, were likely to have been a part of their children’s lives before their imprisonment, and most will soon be returning to the community and to their children. Research has shown that it is in the best interests of the mothers and the children to maintain a relationship across the prison bars. In this article, we use the example of New York State to show how institutional policies and structures can impede or encourage efforts to maintain ties between women and their children and why demonstrating support for family ties must extend well beyond having visiting hours.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1751-9020.2010.00291.x
Keywords: dept.soc; peer-reviewed

Trigger Warnings: From Panic to Data - Laguardia, Francesca; Michalsen, Venezia; Rider-Milkovich, Holly (Journal of Legal Education, 2017)
Keywords: dept.soc; peer-reviewed

Positive Mood and the Perception of Variability Within and Between Groups - Stroessner, Steven J.; Mackie, Diane M.; Michalsen, Venezia (Group Processes & Intergroup Relations, 2005)
Three experiments investigated the effects of positive mood on perceptions of variability within and between groups. Participants formed impressions of two different and highly variable groups under a neutral or positive mood. When participants expected to learn about both groups, positive mood increased perceived intergroup similarity but did not affect perceived intragroup variability. In contrast, when participants expected to learn about only one group, judgments of intergroup and intragroup similarity were both affected by mood. Mood and the intergroup context influenced the nature and degree of information processing and resultant judgments of variability in social groups.
Keywords: dept.soc; peer-reviewed

Are Suicide Attempters Who Self-Mutilate a Unique Population? - Stanley, Barbara; Gameroff, Marc J.; Michalsen, Venezia; Mann, J. John (American Journal of Psychiatry, 2001)
OBJECTIVE: Individuals who mutilate themselves are at greater risk for suicidal behavior. Clinically, however, there is a perception that the suicide attempts of self-mutilators are motivated by the desire for attention rather than by a genuine wish to die. The purpose of this study was to determine differences between suicide attempters with and without a history of self-mutilation. METHOD: The authors examined demographic characteristics, psychopathology, objective and perceived lethality of suicide attempts, and perceptions of their suicidal behavior in 30 suicide attempters with cluster B personality disorders who had a history of self-mutilation and a matched group of 23 suicide attempters with cluster B personality disorders who had no history of self-mutilation. RESULTS: The two groups did not differ in the objective lethality of their attempts, but their perceptions of the attempts differed. Self-mutilators perceived their suicide attempts as less lethal, with a greater likelihood of rescue and with less certainty of death. In addition, suicide attempters with a history of self-mutilation had significantly higher levels of depression, hopelessness, aggression, anxiety, impulsivity, and suicide ideation. They exhibited more behaviors consistent with borderline personality disorder and were more likely to have a history of childhood abuse. Self-mutilators had more persistent suicide ideation, and their pattern for suicide was similar to their pattern for self-mutilation, which was characterized by chronic urges to injure themselves. CONCLUSIONS: Suicide attempters with cluster B personality disorders who have a history of self-mutilation tend to be more depressed, anxious, and impulsive, and they also tend to underestimate the lethality of their suicide attempts. Therefore, clinicians may be unintentionally misled in assessing the suicide risk of self-mutilators as less serious than it is.
Keywords: dept.soc; peer-reviewed

Reentry court judges: the key to the court - Salvatore, Christopher, Venezia, Michalsen; Taylor, Caitlin (Journal of Offender Rehabilitation, 2020)
Over the last few decades, treatment-oriented court judges have moved away from being neutral arbitrators in an adversarial court process to treatment facilitators. In the problem-solving court model, judges are part of a more therapeutic treatment process with program participants and a courtroom work group. The shift from the use of the traditional criminal justice process toward the use of more treatment-oriented models for some populations highlights the need to systematically document key elements of treatment court models. In particular, it is important to clearly document the role of Reentry Court Judges because they are a key component of the Reentry Court model. The current study used interviews with members of the courtroom work group, as well as a focus group interview of former participants in the program, to help identify the role of the judge and activities the judge engages. Findings revealed that the judges played a supportive, informal role, balanced with a more formal, authoritarian role, and the judges engaged participants in pre-court meetings, as well as courtroom sessions. Further, the judges facilitated interactions with program participants outside the courtroom, demonstrating that the judge is a core component of success for participants in Reentry Court.
_eprint: https://doi.org/10.1080/10509674.2020.1733164
Keywords: dept.soc; judges; peer-reviewed; probationers; reentry; reintegration; treatment